Fyn knock-down prevents levodopa-induced dyskinesia in a mouse model of parkinson’s disease - Bordone, Melina Paula (2021)
Dopamine replacement by levodopa (L-DOPA) is the most widely used therapy for Parkinson’s disease (PD), however patients often develop side effects, known as L-DOPA-induced dyskinesia (LID), that usually need therapeutic intervention. There are no suitable therapeutic options for LID, except for the use of the NMDA receptor (NMDA-R) antagonist amantadine, which has limited efficacy. The NMDA-R is indeed the most plausible target to manage LID in PD and recently the kinase Fyn, one of its key regulators, became a new putative molecular target involved in LID. The aim of this work was to reduce Fyn expression to alleviate LID in a mouse model of PD. We performed intrastriatal delivery of a designed micro-RNA against Fyn (miRNA-Fyn) in 6-OHDA-lesioned mice treated with L-DOPA. The miRNA-Fyn was delivered either before or after L-DOPA exposure to assess its ability to prevent or revert dyskinesia. Preadministration of miRNA-Fyn reduced LID with a concomitant reduction of FosB-DFosB protein levels, a marker of LID, as well as decreased phosphorylation of the NR2B-NMDA subunit, which is a main target of Fyn. On the other hand, post-L-DOPA delivery of miRNA-Fyn was less effective to revert already established dyskinesia, suggest-ing that early blocking of Fyn activity might be a more efficient therapeutic approach. Together, our results provide proof of concept about Fyn as a plausible therapeutic target to manage LID, and validate RNA si-lencing as a potential approach to locally reduce striatal Fyn, rising new perspectives for RNA therapy interventions in PD.